PENGARUH LINGKUNGAN BELAJAR DAN KREATIVITAS BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA NEGERI 3 PEMATANGSIANTAR T.A 2024/2025 - Sonjaya Panjaitan; Herlina H. Sianipar; Tumpal Manahara Siahaan (JURNAL ILMIAH NUSANTARA, 2024)
The problem in this study is whether there is an influence of the Learning Environment and Learning Creativity on the Learning Outcomes of Economics of Class XI IPS of SMA Negeri 3 Pematangsiantar. This study aims to determine the influence of the Learning Environment and Learning Creativity on the Learning Outcomes of Economics of Class XI IPS of SMA Negeri 3 Pematangsiantar. The population in this study were all students of class XI IPS as many as 4 classes with a total of 113 students. Sampling was carried out using the total sampling technique so that the sample taken was 88 people.The instrument used in this study was a questionnaire. The validity of the research instrument was tested using the product moment correlation formula for the questionnaire. The reliability of the research instrument was tested using the Alpha formula, which was 0.54 for the Learning Environment and 0.60 for the Learning Creativity questionnaire.Testing of analysis requirements is done by normality and linearity tests. Normality test using Chi Square test, based on the calculation of both normally distributed variables. Linearity test is done by F test, the results show linear and meaningful regression. The results of the analysis show that there is a significant and positive relationship between the learning environment and student learning outcomes with a simple linear regression equation Ῡ = 61.55 + 0.51 X1 and learning creativity with student learning achievement with a simple linear regression equation Ῡ = 61.55 + 0.56 X multi-mediator regression of learning environment and learning creativity with learning outcomes Ῡ = 49.00 + 0.39 X1 + 0.43 X2 For the accuracy of the analysis, the regression linearity test is used. Through the F test, it turns out that Y on X1 and Y on X2 and the regression of Y on X1 and X2 are all linear, so there is no need to look for non-linearity.Thus it can be concluded that this study accepts Ha and rejects Ho. So it can be stated that the learning environment and learning creativity with student learning outcomes in Economics subjects have a significant relationship.Hopefully, with this abstract explanation, you can understand the essence of the research that has been conducted.